PO7 Chromatographic profile analysis of valerian-based phytotherapeutic products marketed in Bogotá, Colombia - Rodriguez Quinche, Maria Catalina; MODESTI COSTA, Geison (Revista Productos Naturales, 2025)
The market for phytotherapeutic products has grown significantly; however, quality control remains a challenge. In Colombia, valerian is one of the most commonly used plants in these products. This study aims to evaluate the chromatographic profiles of Valeriana officinalis and Valeriana pavonii products in Bogotá using HPTLC. Initial differences in the presence of valepotriates suggest a lack of uniformity in composition. The research will continue with more samples and advanced analytical techniques to strengthen quality control and ensure the safety of these products.